Problem-solution framework of retirement planning: A Malaysian perspective - Nur Nadiah Salihah, Mat Razali; Fernando, Yudi (Inderscience Enterprises Ltd., 2022)
This paper aims to review the obstacles faced by individuals in planning a prosperous retirement and to suggest some improvements to encourage the individuals and governments in achieving steadfast finances during the current economic crisis. This paper has utilised a critical review technique on current and emerging systems of retirement planning in Malaysia. We found the two main factors of retirement planning, perceived financial literacy and perception of health, from the literature. Paradoxically, we found limited ways on how the retirement planning practices can assist Malaysians achieve the significance levels of retirement planning which are defined as the successful retirement planning indicators. Contributions of this study are to provide a foresight framework to solve the current Malaysian problems in managing their retirement plan: low salary, late planning, high bankruptcy cases, high household debt and low savings; and suggest a solution framework of study the retirement systems. The literature on retirement planning management has expanded. However, future research is necessary to align the volatile economic conditions and the technological changes.